BNIP3 is degraded by ULK1-dependent autophagy via MTORC1 and AMPK - Park, Chang Wook (Landes Bioscience, 2013)
BNIP3 (BCL2/adenovirus E1B 19 kDa interacting protein 3) is an atypical BH3-only protein that is induced by hypoxia-inducible factor 1 (HIF1) under hypoxia. BNIP3 is primarily regulated at the transcriptional level. However, little is known about the underlying mechanism of BNIP3 degradation. In this study, we found that BNIP3 was downregulated when hypoxia was accompanied by amino acid starvation. The BNIP3 downregulation did not occur at the transcription level and was independent of HIF1A. BNIP3 was primarily degraded by the proteasome, but BNIP3 was subjected to both proteasomal and autophagic degradation in response to starvation. The autophagic degradation of BNIP3 was dependent on ATG7 and MAP1LC3. We determined that autophagic degradation of BNIP3 was specifically regulated by ULK1 via the MTOR-AMPK pathway. Moreover, we confirmed that BNIP3 could play a protective role in tumor cells under hypoxia, and the treatment with Torin1, an MTOR inhibitor, decreased the BNIP3 level and enhanced the death of hypoxic tumor cells.